2021
DOI: 10.1111/cen.14583
|View full text |Cite
|
Sign up to set email alerts
|

The effects of glucagon‐like peptide (GLP)‐1 receptor agonists on weight and glycaemic control in Prader–Willi syndrome: A systematic review

Abstract: Objective The mainstay management of hyperphagia and obesity in Prader–Willi syndrome (PWS) relies on dietary restrictions, strict supervision and behavioural modifications, which can be stressful for the patient and caregiver. There is no established pharmacological strategy to manage this aspect of PWS. Theoretically, glucagon‐like peptide‐1 (GLP‐1) receptor agonists (GLP1‐RA) used in patients with obesity and type 2 diabetes mellitus (T2DM) may be efficacious in weight and glycaemic control of PWS patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Furthermore, 10 patients were treated with a combination therapy of a glucagon-like peptide 1 (GLP-1) receptor agonist due to uncontrolled diabetes. A recent systematic review has shown that GLP-1 receptor agonists are safe in patients with PWS and may potentially help with weight reduction, blood sugar control, and appetite control [ 15 ]. In our cohort, GLP-1 receptor agonists appeared to be well tolerated with no serious adverse effects; however, four patients discontinued the injections because their parents did not feel they had a significant effect on appetite, although these patients had a slightly lowered Hba1c during the early phase of the injection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 10 patients were treated with a combination therapy of a glucagon-like peptide 1 (GLP-1) receptor agonist due to uncontrolled diabetes. A recent systematic review has shown that GLP-1 receptor agonists are safe in patients with PWS and may potentially help with weight reduction, blood sugar control, and appetite control [ 15 ]. In our cohort, GLP-1 receptor agonists appeared to be well tolerated with no serious adverse effects; however, four patients discontinued the injections because their parents did not feel they had a significant effect on appetite, although these patients had a slightly lowered Hba1c during the early phase of the injection.…”
Section: Discussionmentioning
confidence: 99%
“…51,52) which accounts for 7% of the causes of death in patients with PWS. 47) Previous metaanalysis or systematic review results for BMI were various, [12][13][14][15] our study showed a nonsignificant decrease in BMI. These results may be caused by nonsignificant increments in weight and obvious increments in height.…”
Section: Discussionmentioning
confidence: 51%
“…8) In previous systematic reviews and meta-analysis, the effects of pharmacological treatments on body composition variables such as height, BMI, and FM have evaluated. [12][13][14][15] As a result of previous meta-analysis, increased LBM and decreased FM were consistently observed. [12][13][14][15] Since previous studies have investigated randomized controlled trials (RCTs) and nonrandomized controlled trials (NRCTs) simultaneously, [12][13][14][15] biases were unpreventable.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Limited data exist on the outcomes of intensive weight loss interventions in individuals with PWS. Case reports and case series have documented successful weight loss following initiation of GLP-1 receptor agonists [ 7 , 8 ], but data regarding other options are limited. As such, the aims of this retrospective review of real-world clinical data are to examine the efficacy, safety, and tolerability of intensive medical weight loss interventions in individuals with PWS.…”
Section: Introductionmentioning
confidence: 99%